Analysis of topography, heat flow against crustal age in the Southwest Subbasin, South China Sea. Issue 7 (23rd May 2020) - Hu, Litian; Zhang, Peizhen; Hao, Tianyao; Tian, Yuntao; Zhang, Dongli; Li, Zhigang; Li, Xiaolin
ABSTRACT: The relationships in ocean depth and heat flow with crustal age place valuable constraints on the thermal evolution of the oceanic lithosphere. This work aims to establish the relationships for the V-shaped Southwest Subbasin, the southwestern end of the South China Sea formed during 23.6–16 Ma. Using high-resolution multichannel seismic profiles and heat flow measurements, we calculate sediment-corrected topography and heat flow, which are then plotted against crustal age to establish their relationships. The results show that the post-spreading volcanism in the South China Sea influences less on the present-day heat flow than topography. In addition, the topography data are evidently deeper and heat flow data are much lower in the Southeast Asian marginal seas than other oceans. Previous explanation suggested that the abnormal features resulted from lateral heat loss, which would predict a deeper lithosphere–asthenosphere boundary and a high slope in topography and heat flow with age, contrary to the observations. Possible explanations for the abnormal features of the Southeast Asian marginal seas include (1) lack of long-time upwelling magma at the onset of spreading, and (2) reduced magma supply during the seafloor spreading.